Evaluation of The Physical Quality of Banana Peel Extract (Musa paradisiaca) in Cream for Fissures Heels - Khomaini, Khomaini; H, Syaifiyatul; Uswatun Hasanah, Naili (Berkala Ilmiah Kimia Farmasi, 2022)
Banana peel (Musa paradisiaca) was a plant that contained flavonoid compounds. This research used an experimental laboratory method. The cream formulation was made with variations in the concentration of banana peel ethanol extract at 5%, 10%, and 15%. The banana peel extract was obtained by maceration using 70% ethanol as the solvent. The higher the concentration of banana peel extract used, the more it affected the spreadability, which decreased, and the temperature stability met the parameters of each test. Based on the observation data, it was concluded that the difference in the concentration of banana peel ethanol extract as an active ingredient affected the evaluation test parameters, including organoleptic tests, pH tests, spreadability tests, and temperature stability tests. However, all formulas met the evaluation parameters of each test, so they could be formulated into cream preparations as a treatment for cracked and dry heels. The research on the cream preparation of banana peel ethanol extract used the maceration method. It could be concluded that the banana peel ethanol extract cream preparation met the stable physical test parameters and had moderate activity.Keywords: Cream, Physical Quality, Banana Peel Extract, Fissures Heel